2004
DOI: 10.1002/asi.20082
|View full text |Cite
|
Sign up to set email alerts
|

Trend detection through temporal link analysis

Abstract: Although time has been recognized as an important dimension in the co-citation literature, to date it has not been incorporated into the analogous process of link analysis on the Web. In this paper, we discuss several aspects and uses of the time dimension in the context of Web information retrieval. We describe the ideal casewhere search engines track and store temporal data for each of the pages in their repository, assigning timestamps to the hyperlinks embedded within the pages. We introduce several applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Amitay et al [1] have also identified aspects of temporal locality in Web domains, showing that incorporating hyperlink timestamps into link-based page-ranking algorithms can improve retrieval accuracy.…”
Section: Background and Related Workmentioning
confidence: 97%
“…Amitay et al [1] have also identified aspects of temporal locality in Web domains, showing that incorporating hyperlink timestamps into link-based page-ranking algorithms can improve retrieval accuracy.…”
Section: Background and Related Workmentioning
confidence: 97%
“…Hearst's book presents a comprehensive analysis of user interface design to search the live web but searching over historical web collections is not addressed [10]. For instance, the date of publication is mandatory on any news article, but very hard to identify on a typical web page [3,5]. Note that the date of publication is crucial to enable users to explore the temporal perspective of data.…”
Section: Related Workmentioning
confidence: 99%
“…There has been some research activity also in the area of "temporal link analysis", mostly done on WWW pages. In [6] the authors present several aspects and uses of the time dimension in the context of Web IR. K. Berberich et al [7] argue that the freshness of web content and link structure is a factor that needs to be taken into account in link analysis when computing the importance of a page.…”
Section: Related Workmentioning
confidence: 99%